2014
DOI: 10.5296/bms.v5i1.5267
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Decision Making: Process, Models, and Theories

Abstract: The theories and models underpinning strategic decision-making (SDM) are somewhat eclectic that demand multidisciplinary approach and appears non-differential from decision-making (DM) theories. This paper is a first attempt that puts the discipline into perspective of its coherent whole. We start by defining strategy and SDM in order to set the expectations for the rest of the paper. Next, we make an outline on the contribution of management science (MS) to SDM before establishing the relationship with MS and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 56 publications
(41 reference statements)
0
11
0
4
Order By: Relevance
“…However, there is no one pattern that can reveal the cognitive process of decision-makers, and the way they use these phases in OSNs for DM is different. The orders of the DM phases tend to be more anarchical and sequential, following the Mintzberg model [1], [21], factoring in the various dynamics of the DM process and a decision-maker. These results challenge purely rational and anarchical models by recognizing the interweaving of anarchical decision sequences within the structure of rational decision-making phases.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, there is no one pattern that can reveal the cognitive process of decision-makers, and the way they use these phases in OSNs for DM is different. The orders of the DM phases tend to be more anarchical and sequential, following the Mintzberg model [1], [21], factoring in the various dynamics of the DM process and a decision-maker. These results challenge purely rational and anarchical models by recognizing the interweaving of anarchical decision sequences within the structure of rational decision-making phases.…”
Section: Resultsmentioning
confidence: 99%
“…The research shows that most of the decision-making phases identified by Simon [26,27] and Mintzberg [1], [21] are present in HOSNs and FOSNs, but the sequence of these phases tend to be neither purely anarchical nor rational but a blend of both. The findings of the research have significant practical implications for the design of OSNs that support blended decision-making processes by leveraging the wisdom of crowds.…”
Section: Othermentioning
confidence: 94%
See 2 more Smart Citations
“…The multicriteria analysis is deployed in order to support the decision-making with emphasis on the following (Anwar et al, 2014;Montibeller & Franco, 2011;Franco & Rouwette, 2011;Franco & Montibeller, 2010):…”
Section: Generalmentioning
confidence: 99%